Rewritten or Reused? Originality, Intertextuality, and Reuse in the Writings of a Buddhist Visionary in Contemporary Tibet - Terrone, Antonio (Buddhist Studies Review, 2017)
The study of Buddhist texts can inform us of the way scriptures were composed, as well as illuminate the reasons behind their production. This study examines the phenomenon of borrowing and reusing portions of texts without attributing them to their ‘legitimate authors’ within the Buddhist world of contemporary Tibet. It shows that not only is such a practice not at all infrequent and is often socially accepted, but that it is used in this case as a platform to advance specific claims and promote an explicit agenda. Therefore, rather than considering these as instances of plagiarism, this essay looks at the practice of copying and borrowing as an exercise in intertextuality, intended as the faithful retransmission of ancient truths, and as an indication of the public domain of texts in Tibet.